2011
DOI: 10.1007/s11434-011-4484-1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-induced reciprocal transformation in the root phenotype of Oriental ginseng is associated with alteration in DNA methylation

Abstract: Oriental ginseng is an important medicinal plant that grows in 2 major forms or ecotypes, wild and domesticated. Each form differs conspicuously in root phenotype, but can be converted from one type to another by habitat. Here we show that the habitat-induced transformation of ginseng root phenotype was accompanied by alteration in cytosine methylation at a large number of 5′-CCGG-3′ sites detected by the methylation-sensitive polymorphism (MSAP) marker. The collective CG and CHG methylation levels of all 4 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is in contrast to the results for L. japonica and L. japonica var. Chinensis [27], Panax ginseng [31], and Taxus media [21]. These results indicate that DNA methylation in the promoter region of the genes for key enzymes is an important factor in the differences in the quality and gene expression of key enzymes in medicinal plants.…”
Section: Discussionmentioning
confidence: 82%
“…This is in contrast to the results for L. japonica and L. japonica var. Chinensis [27], Panax ginseng [31], and Taxus media [21]. These results indicate that DNA methylation in the promoter region of the genes for key enzymes is an important factor in the differences in the quality and gene expression of key enzymes in medicinal plants.…”
Section: Discussionmentioning
confidence: 82%
“…Chinese ginseng has been regarded as the symbolic “king” of traditional Chinese medicine and cherished for thousands of years [ 17 , 18 , 36 ]. This is because it is widely believed in Chinese herb culture that ginseng has the capacity to boost human stamina and enhance longevity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the morphology of ginseng roots is mainly determined by the habitat, and therefore, the roots of the wild and cultivated plants are well distinguished. It has been recently reported that this habitat-induced reciprocal transformation is accompanied by an alteration in DNA methylation [60] . Additionally, we can suggest that, in three to four nucleoli cells, the biosynthesis is more intensive than in one to two nucleoli cells, because the observed decrease in the nuclei/nucleoli ratio of the area implies the increase in the activity of protein synthesis in the cell [57] .…”
Section: Discussionmentioning
confidence: 97%